Tissue Nutrient Environments and Their Effect on Regulatory T Cell Biology - Blagih, Julianna; Hennequart, Marc; Zani, Fabio (Frontiers in Immunology, 2021)
Regulatory T cells (Tregs) are essential for mitigating inflammation. Tregs are found in nearly every tissue and play either beneficial or harmful roles in the host. The availability of various nutrients can either enhance or impair Treg function. Mitochondrial oxidative metabolism plays a major role in supporting Treg differentiation and fitness. While Tregs rely heavily on oxidation of fatty acids to support mitochondrial activity, they have found ways to adapt to different tissue types, such as tumors, to survive in competitive environments. In addition, metabolic by-products from commensal organisms in the gut also have a profound impact on Treg differentiation. In this review, we will focus on the core metabolic pathways engaged in Tregs, especially in the context of tissue nutrient environments, and how they can affect Treg function, stability and differentiation.